IDENTITY AS A PHENOMENON OF THE POSTMODERN AGE - Stepyko (Степико Михайло Тимофійович), Mykhailo (Politology bulletin, 2019)
This article has analyzed the influence of postmodern practices on the development and functioning of nation states, their culture and identity. It is shown that postmodernism is largely determined by the processes of globalization as the current defining civilizational progress, the content of which is the growing interconnection and interdependence of national economies, political and socio-cultural systems, as well as the identity of universalistic practices of regulating the activity of subjects of world-system relations in different spheres of being.It was found that one of the problematic consequences of postmodernism is the radical transformation of traditional structures and principles of self-identification, both collective and personal wherever they happen, and whatever the institutional, cultural layers of society and patterns of behavior affect people. Close coexistence and even interpenetration of completely different, sometimes mutually exclusive, and sometimes simply disjointed value scales lead to total relativization of everything and everybody when even personal and collective identities lose the quality of metaphysical constants and are perceived as an unfinished project. That is why a person of the postmodern age is deprived of self-certainty. Therefore, there is a great need to rethink the content and consequences of postmodern practices of blurring traditional identities and the emergence of new ones, the role of the state in preserving and protecting the values, contents, ideals, cultural models and language that shape and reproduce the nation.It is concluded that in post-totalitarian states of the European space (including Ukraine), processes of globalization and post-modern practices create two opposite tendencies. On the one hand, globalization unifies, internalizes and westernizes all aspects of society. On the other hand, in the way of bringing the elements of modern democracy into the life of the post-totalitarian state, globalization stimulates the processes of cultural and spiritual revival and the desire to form the collective «We», affirm its identity and individuality through consolidation around a common history, language, culture, values and orientations, life strategies. In Ukraine, it is also a consolidation of the efforts of all its citizens to repel Russian aggression, protect the sovereignty and independence of the state, integrate into European and Euro-Atlantic structures, achieve well-being for all citizens. Ukraine, as the newest unfinished civilization project, has all prospectives of avoiding the pitfalls of both «melting pot» and multiculturalism, as well as postmodern problems, since most of them have not yet attained a broad realization in its territory.

У статті проаналізовано вплив посмодерністських практик на розвиток та функціонування національних держав, їх культуру та ідентичність. Показано, що постмодернізм багато в чому визначається процесами глобалізації як визначальному сьогодні цивілізаційному поступу, змістом якого є зростаючий взаємозв’язок та взаємозалежність національних економік, політичних та соціо-культурних систем, а також тотожність універсалістських практик регулювання діяльності суб’єктів світосистемних відносин в різних сферах буття.З’ясовано, що одним із проблемних наслідків постмодернізму, — де б вони не відбувалися, і які б інституційні, культурні пласти суспільства й моделі поведінки людей не зачіпали — є радикальне перетворення традиційних структур і принципів самоідентифікації, як колективної, так і особистої. Тісне співіснування і навіть взаємопроникнення абсолютно різних, іноді взаємно ексклюзивних, а іноді і просто непересічних ціннісних шкал призводить до тотальної релятивізації всього і вся, коли навіть і особиста, і колективна ідентичність втрачають якість метафізичних констант і усвідомлюються як «незавершений проект». Саме тому людина епохи постмодерну позбавляється впевненості щодо власної визначеності. Тому доконечною є потреба переосмислення змісту та наслідків посмодерністських практик розмивання традиційних ідентичностей та появу нових, ролі держави у збереженні та захисту цінностей, змістів, ідеалів, культурних зразків та мови, що формують та відтворюють націю.Підсумовується, що в посттоталітарних державах європейського простору (в тому числі і в Україні) процеси глобалізації та практики посмодерну породжують дві протилежні тенденції. З одного боку, глобалізація уніфікує, інтернаціоналізує та вестернізує всі сторони життєдіяльності суспільства. А з іншого, вносячи у життя посттоталітарної держави елементи сучасної демократії, стимулює процеси культурного й духовного відродження та прагнення до формування колективного «Ми», утвердження його самості та окремішності шляхом консолідації навколо спільної історії, мови, культури, цінностей та орієнтацій, життєвих стратегій. В Україні це ще й консолідація зусиль усіх її громадян для відсічі російській агресії, захисту суверенітету та незалежності держави, її інтеграції до європейських та євроатлантичних структур, досягнення гідного людини добробуту для всіх громадян. Україна як новітній незавершений цівілізаційний проект має всі перспективи уникнути пасток як «плавильного казана» та мультикультуралізму, так і проблем постомодерну оскільки більшість із них ще не набула на її теренах широкого втілення.
ІДЕНТИЧНІСТЬ ЯК ФЕНОМЕН ЕПОХИ ПОСТМОДЕРНУ
Keywords: postmodern; nation; collective and personal identity; globalization; challenges to Ukrainian identity; посмодерн; нація; колективна та особистісна ідентичність; глобалізація; виклики українській ідентичності